Influence of the external wall on the airborne sound insulation in buildings - SZUDROWICZ, B.; IŻEWSKA, A. (Archives of Acoustics, 1996)
The external wall, just as all the other partitions in the building, takes part in the sound transmission by the flanking structural path. Depending on the construction of the external wall, its influence on the total value of the airborne flanking transmission may be different. The papers presents two different solutions of the external walls: 1) walls which may be considered as panels and 2) multi-layer partitions, where the direct sound insulation is clearly lowered near the resonance frequency existing in the range of the frequencies found in buildings. The analysis considered both the calculation formula according to the EN standard [1] as well as the results of our own measurements performed in the building.